2007
DOI: 10.1177/0193945907302981
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Incarcerated and Community-Dwelling Older Men's Health

Abstract: The purpose of this study is to compare incarcerated and community-dwelling older men's self-efficacy for health management, health-promotion behaviors, and health status. Social cognitive theory was the guiding framework. A sample of 51 incarcerated and 33 community men (age 50 and older) were surveyed. Frequencies and independent samples t tests were computed. Inmates reported significantly less participation in health-promotion behaviors (p < .01) and attended fewer programs (p < .05). The two groups did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…These records belonged to 203 older prisoners (>50 years) and 203 younger prisoners (≤49 years). Older prisoners were defined as those 50 years and older in accordance with available literature [5,7,8]. Research ethics commission (REC) approval was sought and obtained from 10 regional RECs in Switzerland, where the relevant prisons are located.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These records belonged to 203 older prisoners (>50 years) and 203 younger prisoners (≤49 years). Older prisoners were defined as those 50 years and older in accordance with available literature [5,7,8]. Research ethics commission (REC) approval was sought and obtained from 10 regional RECs in Switzerland, where the relevant prisons are located.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing and ageing population of prisoners is evident in many countries, and the most prominent changes are seen among the prisons in the USA [2] and the UK [4]. Due to accelerated ageing, older prisoners are defined as those who are aged 50 years and over [5,6], rather than 65 years and older in the community; because a 50-year-old prisoner tends to represent the health burden of someone who is 10-15 years older in the community [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Palliative care and information and counseling about end-of-life options are needed in prison, especially since many older adults in prison are chronically ill, including with dementia, and a sizable number (e.g. 5,000 in the USA) die each year while in prison (Loeb et al, 2008;Maschi et al, 2012c;Williams and Abraldes, 2007).…”
Section: Older Compared To Younger Prisonersmentioning
confidence: 99%
“…Studies comparing inmates and the general population have been challenged by a lack of comparable data across populations and by the lack of detailed data to adequately account for potential confounders. 7,31,54 The systematic exclusion of inmates from large epidemiological studies could lead to under-estimation of the prevalence of conditions such as HIV found more commonly in African-American and Latino men, who are underrepresented in health research 55,56 but over-represented in the criminal justice system. Thus, the exclusion of inmates from broader health research may decrease the accuracy of population health statistics and measurement of population health disparities, as described in work by Edlin and Carden for hepatitis C. 57 Most literature documenting the existence of racial and ethnic health disparities has been derived from non-institutionalized participants and has not measured whether participants have had criminal justice exposure.…”
Section: Knowledge Gaps and Research Opportunitiesmentioning
confidence: 99%